Information Technology Audit at XYZ Agency, a Government Institution, Using COBIT 5 Framework in Domain Delivery, Service and Support - Joe Yuan Mambu; Gideon Fernando Tengker; Erienika M Lompoliu; Axcelino Langi (Universitas Negeri Medan, 2021)
Technology has become an important component used by humans to facilitate them in finishing work in this digital era. XYZ institution utilizes technology, especially in the field of e-government to help each employee in doing their duties and responsibilities. In carrying out the responsibility as a government agency especially that is involving or related to the field of information technology may sometimes encounter problem. To find out the extent of information technology management in the XYZ institution, an audit is required. An audit, in the form of COBIT 5 framework within the DSS Domain, was carried out to oversee the work as well as infrastructure management within the information technology area in the XYZ institution. The result of the audit conclude that the within the DSS domain the organization reached level 2 which means task are being done but not yet managed by the organization. There are rooms for improvement by establishing the process through standard operation procedures (SOP).